2017
DOI: 10.1016/j.future.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal tumour simulation using agent based modelling and high performance computing

Abstract: 450,000 European citizens are diagnosed every year with colorectal cancer (CRC) and more than 230,000 succumb to the disease annually. For this reason, significant resources are dedicated to the identification of more effective therapies for this disease. However, classical assessment techniques for these treatments are slow and costly. Consequently, systems biology researchers at the Royal College of Surgeons in Ireland (RCSI) are developing computational agent-based models simulating tumour growth and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Hence, we also extended the study to perform a comprehensive global fitting of the model using Bayesian parameter fitting techniques to two novel experimental data sets (producing normalised root squared mean errors of 0.38 and 0.24). This was made possible due to the economic computational cost of running our model, though we note that there have been recent advances in the simulation of more holistic cellular automaton models 23 . It may even be possible to calibrate such models with spatio-temporal data in the near future though it will require careful acquisition of three dimensional in vivo imaging data for effective calibration as discussed in 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we also extended the study to perform a comprehensive global fitting of the model using Bayesian parameter fitting techniques to two novel experimental data sets (producing normalised root squared mean errors of 0.38 and 0.24). This was made possible due to the economic computational cost of running our model, though we note that there have been recent advances in the simulation of more holistic cellular automaton models 23 . It may even be possible to calibrate such models with spatio-temporal data in the near future though it will require careful acquisition of three dimensional in vivo imaging data for effective calibration as discussed in 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of elements that were not considered in other investigations [ 13 , 14 , 15 , 16 , 21 ] allowed us to obtain a more adjusted model in terms of the functionality conditions. Some of the results concurred with behaviors that have already been described in other studies, while others enabled us to identify values that did not correspond with the results reported by other authors due to their simplifications.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding research in the field of computational simulation, most of the studies reviewed focused on the modeling of nanostructured biosensors [ 13 , 14 , 15 ], showing mathematical models and the results of simulations of the characteristics of the biosensor without specifically mentioning their application in the early detection of diseases. On the other hand, there were studies found on cancer evolution models based on agents and implementing high-performance computing (HPC) [ 16 , 17 ], as well as the progression of melanoma [ 18 ], evolution of metastatic processes, tumor angiogenesis [ 16 ], treatment response [ 19 , 20 ] and simulation of the adherence of therapeutic particles [ 21 ], evidencing efforts that are much more oriented toward the treatment and description of the evolution of CRC, which is oriented toward the early diagnosis of the description of the behavior of biomarkers in a dynamic domain.…”
Section: Introductionmentioning
confidence: 99%
“…Several other agent-based models have been described and used in related studies. An agent-based model focused on stem cell dynamics in the colon crypt has been developed ( 61 ) and an agent-based model has been developed and colorectal tumor growth stimulated on a high-performance computer with the intention, in the future, of optimizing therapeutic strategies ( 62 ). A multiscale agent-based model has been used to investigate the synergistic effects of a large space of dose combinations using local and global optimization algorithms ( 63 ).…”
Section: Discussionmentioning
confidence: 99%